Chemical composition and biological activities of essential oils from the flowers and leaves of Celtis planchoniana KIChr. - Oz, Mehmet; Ucuncu, Osman; Baltaci, Cemalettin; Fidan, M. Said; Karatas, Seyda Merve (Taylor & Francis Ltd, 2023)
Most plant parts are used in traditional food and medicine. Plants are significant resources of potential phytochemicals. This study investigated the properties of essential oil, antioxidant, and antimicrobial activities of the flowers and leaves of the Celtis planchoniana plant. Based on the GC/MS-FID analysis of essential oils extracted from the flowers and leaves of C. planchoniana, 101 and 91 compounds were identified from their structures, respectively. Chemical classes with the highest percentage of compounds found in essential oils of plants were oil acids, with 31.51% in flowers, and aldehydes, with 32.89% in leaves. Hexadecanoic acid (29.94%) and (E)-2-hexenal (16.11%) compounds were determined as the main components in the plant's flowers and leaves. Among the flower and leaf samples, the highest antioxidant levels were 132.77-80.10 mg AA eq./100 mL in TAC, 17.63-118.23 mg AA eq./100 mL in ABTS, 71.41-85.15 mg GA eq./100 mL in TPC, and 15.08-15.71 mg AA eq./100 mL in DPPH capacity. According to the TFC, TPC, ABTS, DPPH, and FRAP tests conducted to determine the antioxidant properties of C. planchoniana, the essential oil obtained from its leaves demonstrated more significant antioxidant properties than the essential oil obtained from its flowers. According to the antimicrobial activity analysis, the leaf and flower essential oil samples exhibited no antimicrobial activity against the microorganisms tested.
Keywords: Antimicrobial activity; antioxidant activity; Celtis planchoniana; chemical composition; essential oil